Difficulties in conducting pure academic research, obstacles in data collection and quality of informations: The example of the INTERCEPTOR study. (October 2019) - Merlano, M.; Denaro, N.; Benasso, M.; Licitra, L.; Bossi, P.; Locati, L.; Vecchio, S.; Bruzzi, P.
Highlights: Interceptor trial compared concurrent chemoradiotherapy with induction chemotherapy followed by Cetuximab RT. We reported difficulty in data collection among centers with low experience. Expertise is needed in the treatment of LASCCHN. Differences in accrual and quality of data reflect expertice of participating centers and number of published papers of each PI. Abstract: Purpose/Objective: On September 2009: We started a randomized multicenter phase III study comparing chemoradiation (CRT) (Aldestein RTOG regimen) versus induction chemotherapy followed by Cetuximab radiation (IBRT). The main study's aim was comparison of overall survival but no formal analyses have been made between the two arms because of low accrual and high amount of missing data. The goal of this paper is to identify the reasons of difference in accrual and quality of data among participating centers. Material/Methods: Statistic: We correlated data collection quality with relevance of the centers, accrual and number of scientific papers (both specific on HNC and other topics) of each PI. We created an HNC publishing score dividing the number of HNC specific papers for the overall number of published papers. Results: We observed a strong difference in the accrual of pts as well as in the quality of data among the participating centers. The accrual was independent from the quality of data since some centers with low accrual produced high quality data with an excellent follow up. We found a correlation among both number of published papers of each PI and HNC publishing score with the quality of data. Conclusion: The study demonstrated that expertise in HNC is important not only to ensure a better outcomes but also to provide high quality data in phase III trials.